2019
DOI: 10.1111/febs.15152
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of HNF4α during intestinal epithelial differentiation is involved in the activation of ER stress

Abstract: Intestinal epithelial cells are derived from stem cells at the crypts that undergo differentiation into transit‐amplifying cells, which in turn form terminally differentiated enterocytes as these cells reach the villus. Extensive alterations in both transcriptional and translational programs occur during differentiation, which can induce the activation of cellular stress responses such as ER stress‐related unfolded protein response (UPR) and autophagy, particularly in the cells that are already committed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
3
0
3
Order By: Relevance
“…Hepatocyte nuclear factor 4 alpha (HNF4α) is expressed in intestinal villi (Stegmann et al, 2006) and has been identified as a transcription factor that regulates the expression of genes during intestinal cellular differentiation during endoderm development (Yao et al, 2016). It was recently discovered that HNF4α is involved in the activation of ER stress during intestinal epithelial differentiation (Tunçer et al, 2019), demonstrated by the upregulation of XBP1 and ATF6 (two ER stress mediators) downstream of HNFα activity. This study is important because it ties together the importance of ER stress in maintaining proper ISC proliferation and differentiation (Heijmans et al, 2013) with the fact that HNF4α is expressed in the intestinal villi (Stegmann et al, 2006), which suggests that these two signaling pathways are essential for ISC fate and fitness.…”
Section: Hypoxia and Er Stress As Drivers Of Epithelial Repair And DImentioning
confidence: 99%
“…Hepatocyte nuclear factor 4 alpha (HNF4α) is expressed in intestinal villi (Stegmann et al, 2006) and has been identified as a transcription factor that regulates the expression of genes during intestinal cellular differentiation during endoderm development (Yao et al, 2016). It was recently discovered that HNF4α is involved in the activation of ER stress during intestinal epithelial differentiation (Tunçer et al, 2019), demonstrated by the upregulation of XBP1 and ATF6 (two ER stress mediators) downstream of HNFα activity. This study is important because it ties together the importance of ER stress in maintaining proper ISC proliferation and differentiation (Heijmans et al, 2013) with the fact that HNF4α is expressed in the intestinal villi (Stegmann et al, 2006), which suggests that these two signaling pathways are essential for ISC fate and fitness.…”
Section: Hypoxia and Er Stress As Drivers Of Epithelial Repair And DImentioning
confidence: 99%
“…At a tau value threshold of >0.85, we identified 140 TFs displaying cell-type-specific expression ( Figure 1C ), including BCL11A and PAX5 in B cells, FOXP3 and LEF1 in T cells, JDP2 , PRNP , and SOX10 in enteric glial cells, CDX2 , EHF , and HNF4A in epithelial cells, and SOX17 in VECs. Among the identified TFs, many have been implicated in corresponding cell types in other species, e.g., HNF4A ( Boyd et al, 2009 ; Tunçer et al, 2020 ), SOX17 ( Yao et al, 2019 ), and PAX5 ( Cobaleda et al, 2007 ; Medvedovic et al, 2011 ) are essential for intestinal epithelial cell, VECs, and B cell differentiation, respectively. Furthermore, several TFs displayed age-dependent expression patterns (Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…53 Altay kulübünün düzenlediği voleybol, atletizm, bisiklet yarışmalarında dereceye giren sporculara İzmir Türk Ocağında hediye ve ödülleri verilmiştir. 54 Ödemiş Türk Ocağı'nda spor faaliyetleri 1923 yılında kurulan Altınova Güç Yurdu Spor Kulübünün kurulmasıyla başlamıştır. 1928 yılında Küçük Menderes, 55 1930 yılında Yıldırım Spor Ödemiş Türk Ocağı himayesinde faaliyetlerini sürdüren diğer gençlik kulüpleri oldular.…”
Section: -Ocakların Bünyesinde Kurulan Spor Kulüpleri Ile Ocakların H...unclassified
“…107 Turgutlu'da da belediye Kasaba Türk Ocağı'na, 13.000 metrekarelik bir spor sahası bağışlamış, bunun dışında 800 lira da para yardımında bulunmuştur. 108 Kasaba (Turgutlu) Türk Ocağı spor sahasının yapılması için müsamere gibi gelir getirici etkinliklerde düzenlemiştir. 109 Nazilli Türk Ocağı 1926 yılında binasına bilardo masası getirerek, bir bilardo salonu oluşturmuş, bilardo oyunu için malzeme siparişi vermiştir.…”
Section: -Spor Sahasına Sahip Olan Türk Ocağı şUbeleriunclassified